Allah : a Christian response - Volf, Miroslav (New York : HarperOne, 2011)
"ALLAH offers a constructive vision for a new pluralism. The claim that Muslims and Christians worship the same God yet have different understandings of that one God is an expression of just such pluralism. If a "clash of civilizations" is good for fighting each other, this new pluralism is good for building a common future together. Volf is ideally suited to reach a large, motivated audience for this book. He is leading expert about religion and conflict and is the chief spokesperson for The Common Word, the world's leading interfaith dialogue initiative between Christians and Muslims that has been unprecedented in its importance, scope and global traction. An ongoing project, The Common Word has spawned conferences at leading institutions around the world, a documentary film, specialty books, and a robust online community"--
Includes bibliographical references (p. [267]-314) and index.
Keywords: God (Islam); God (Christianity); Islam -- Relations -- Christianity; Christianity and other religions -- Islam; RELIGION / General